Internet Resources as a Source of Parents’ Representations About the Problems of Development, Education and Treatment of Early age Children with Special Needs - Valitova, Irina (Psychological Prospects Journal, 2019)
The features of communication between parents of early age children and children with special needs are analyzed in social networks and on Internet forums. It has been established that everyday parents’ representations about the problems of development of young children and children with special needs combine the features of science and validity with those of bias and mythology, which corresponds to the characteristics of everyday consciousness.The article describes the results of two studies conducted using content-analysis. The results of the content- analysis of the parents’ representations about problems in development and behavior of normally developed young children are presented. It is established that the most discussed are problems with sleep, behavior and organization of nutrition of young children. On the Internet, parents pay attention to the description of problems and how to solve them, but they rarely try to analyze the causes of problems that arise. Parents more often see the origins of problem behavior in the child and its features than in their own actions.The results of the content analysis of the communication of mothers with children with special needs are also presented. Mothers turn to online resources to obtain information about their child’s development, treatment options, methods, institutions, and specialists providing effective assistance and support. Social networks perform the function of support, creating emotional resources for mothers to provide for the treatment and upbringing of a child with special needs.The analysis of parents’ communication on the Internet is an important source for understanding the content of their everyday representations about the child, its treatment and upbringing. Analysis of forum discussions and social networking can be used by professionals to improve the quality of interaction with parents as a doctor’s patient and clients of a psychologist.
Keywords: early age children; children with special needs; social networks; Internet forums; everyday consciousness; parents of children with special needs; parents’ representations